Clinical factors associated with postoperative complications and the functional outcome in mandibular reconstruction. Issue 5 (9th April 2013) - Tsuchiya, Sunao; Nakatsuka, Takashi; Sakuraba, Minoru; Kimata, Yoshihiro; Sakurai, Hiroyuki; Nakagawa, Masahiro; Takushima, Akihiko
<x xml:space="preserve">Abstract</x> Background Few studies have performed a multiple factor analysis to assess the factors associated with successful mandibular reconstructions in a large number of subjects. The purpose of this study is to evaluate the functional outcome in mandibular reconstruction by means logistic regression analysis. Methods Since April 2005 to September 2009, 126 patients underwent segmental resection of the mandible for cancer ablation and mandibular reconstruction with free flaps at 6 Japanese institutions. The patients' charts were reviewed retrospectively. Twelve patients were excluded for the reconstruction was with double flaps, or they went under secondary reconstruction. With logistic regression analysis in 114 subjects, we assessed multiple factors influencing postoperative speech intelligibility, feeding ability, and postoperative complications of mandibular reconstruction. Results The use of a reconstruction plate with a soft‐tissue free flap only was showed to have a deleterious effect on postoperative feeding. The strong association in the level of statistical significance between the use of a reconstruction plate with soft‐tissue free flaps only and the occurrences of major complications was indicated. It was also statistically revealed that the postoperative presence of opposing teeth contributed to both speech intelligibility and oral intake. Conclusions In our research, osteocutaneous flaps were superior to reconstruction plates with soft‐tissue free flaps regard to the postoperative feeding ability and major complication rate. © 2013 Wiley Periodicals, Inc. Microsurgery 33:337–341, 2013.